Formulation of Gammaoryzanol-Loaded Nanoparticles for Potential Application in Fortifying Food Products - Serveh Ghaderi; Saeed Ghanbarzadeh; Zahra Mohammadhassani; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2014)
Purpose: The field of nanoparticle delivery systems for nutrients and nutraceuticals with poor water solubility has attracted a great attention during the last decades. Methods: Ethyl cellulose (EC) based GO-loaded nanoparticles were prepared by solvent evaporation method. The effects of formulation parameters on nanoparticle size, encapsulation efficiency (EE%) and loading efficiency (LE%) were investigated. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) techniques were used to investigate the crystalline behavior of GO and EC after the preparation of nanoparticles. Stability of the prepared nanoparticle was investigated during five weeks of storage. Results: Particle sizes of all formulation were in the range of 70-100 nm with narrow size distribution. Increase in the time of sonication from 1 to 5 minutes decreased the particle size. However, the mean particle size was increased when the sonication time increased from 5 to 7 minutes. The results showed that in the same concentration of PVA, increasing the ratio of EC:GO led to an increase in the GO encapsulation efficiency and decrease in loading efficiency. During five weeks, the mean diameter and size distribution indexes (SPAN values) of nanoparticles did not show significant changes. DSC and XRD studies indicated that crystallinity of GO was decreased in nanoparticles. Conclusion: EC based nanoparticles are promising carriers for addition of GO as a water insoluble antioxidant to fortify liquid food products without any change in quality of products.